Reduction in the level of antibodies against heat shock proteins 60 during different hormonal protocols in postmenopausal women - Rajtar-Ciosek, Agnieszka; Kacalska-Janssen, Olga; Zmaczyński, Andrzej; Wyroba, Jakub; Tomczyk, Rita; Wiatr, Joanna; Gałuszka-Bednarczyk, Anna; Bereza, Tomasz; Milewicz, Tomasz; Krzysiek, Józef (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: In current literature, the immune-inflammatory theory of atherosclerosis is widely discussed. The role of how heat shock proteins 60 (HSP60) lead to the development of the atheromatous plaque is especially underlined. The aim of the study is to estimate the influence of three hormonal protocols on behavior of antibodies against HSP60. It determines the state of endothelium in postmenopausal women. Material and methods : The study was carried out on 90 women between 2007 and 2012. All the women were in their menopausal age (51 ± 3 years), from the south region of Poland, with a follicle stimulating hormone (FSH) level above 25 mIU/ml, and with menopausal symptoms disturbing their normal daily activity. The study was done for a period of 6 months. Three groups of 30 randomized patients were formed. In the first group we used transdermal estrogen therapy in a 37.5 µg/24 h dose combined with a 10 mg dose of dydrogesterone. In the second group we applied transdermal estrogen therapy in a 50 µg/24 h dose with 2.5 mg of oral medroxyprogesterone. In both these groups, gestagens were administered continuously. In the third group, we prescribed continuous, oral, low-dose combined estrogen-gestagen therapy with 1 mg of ethinyl estradiol and 0.5 mg of norethisterone acetate. The control group consisted of 30 volunteers who were also from the south region of Poland, in good health, with menopausal symptoms, no menstrual period for the last 12 months, selected considering their age and weight, with an FSH level above 25 mIU/ml and with normal levels of thyroid stimulating hormone (TSH) and prolactin. All patients treated and in the control group were seronegative to Chlamydia pneumonia for the entire duration of the study. In the analysis conducted, nonparametric tests were used (Mann-Whitney U test, Wilcoxon test, Kruskal-Wallis test – ANOVA). Results: After 6 months of hormonal therapy, we found that all schemes of treatment promote a significant reduction in antibodies against HSP60 in all treated groups vs. the control group. Conclusions : All of the investigated estrogen protocols have a favorable impact on the blood level of HSP60 antibodies in early postmenopausal women who have no cardiovascular risk factors. It triggers a better condition of endothelium.